Mild encephalopathy with reversible splenial lesion: Description of nine cases and review of the literature. (May 2021) - Grosset, Lina; Hosseini, Hassan; Bapst, Blanche; Hodel, Jérôme; Cleret De Langavant, Laurent; Faugeras, Frédéric; Bachoud-Lévi, Anne-Catherine; Seddik, Lilia
Abstract: Mild encephalopathy/encephalitis with reversible splenial lesion (MERS) is a transient clinico-radiological syndrome characterized by non-specific encephalopathy and specific magnetic resonance imaging (MRI) pattern. MRI shows an ovoid lesion in the mid-splenium of the corpus callosum (SCC), with signal-intensity anomaly similar to stroke but vanishing within few weeks. Although there are a lot of child MERS cases descriptions, there are just a few adult-onset reported. Our goal is to provide a better clinical and radiological description of this entity. We reported nine adult-onset cases of MERS managed in our stroke unit between 2017 and 2019. The study of our adult series suggests that epilepsy and the context of an infection are very common in MERS. Adult cases show frequent focal neurological deficits and few encephalopathies compared to children. The measurement of very low ADC values in SCC lesion is a new radiological feature of MERS that should be systematically assessed in suspected cases to differentiate this complex syndrome from SCC strokes.